Current appliance of bortezomib in multiple myeloma treatment - Urbanska-Ryś, Halina; Ryś, Monika (Contemporary Oncology/Współczesna Onkologia, 2008)
Multiple myeloma (MM) still remains an incurable malignancy of the lymphoid system. The appliance of new drugs in the therapy of MM, including the proteasome inhibitor bortezomib, changes treatment results and prognosis. Bortezomib (VelcadeTM) is given routinely in the dose of 1.3 mg/m 2 on days 1, 4, 8, 11 of a 21-day cycle in relapsed and refractory MM, but the results of clinical trials suggest its efficacy in the induction phase of the treatment regardless of patient’s age. Bortezomib is effective in monotherapy, but its synergism with other drugs means that it is actually more effective when administered in combinations with dexamethasone, doxorubicin, liposomal, pegylated doxorubicin, cyclophosphamide, thalidomide and lenalidomide. Adverse events observed after bortezomib treatment are usually predictable and manageable. Polyneuropathy diagnosed in about 30% of patients treated with bortezomib imposes dose reduction to 1.0 and 0.7 mg/m 2 and is reversible in most patients after therapy completion.